2015
DOI: 10.1007/s00198-015-3109-y
|View full text |Cite
|
Sign up to set email alerts
|

The position of strontium ranelate in today’s management of osteoporosis

Abstract: Osteoporosis accounts for about 3 % of total European health-care spending. The low proportion of costs for the pharmacological prevention of osteoporotic fracture means that it is highly cost saving, especially in patient with severe osteoporosis or patients who cannot take certain osteoporosis medications due to issues of contraindications or tolerability. Following recent regulatory changes, strontium ranelate is now indicated in patients with severe osteoporosis for whom treatment with other osteoporosis t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
53
0
2

Year Published

2017
2017
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 90 publications
(55 citation statements)
references
References 19 publications
0
53
0
2
Order By: Relevance
“…Strontium Ranelate is effective in increasing BMD in post-menopausal women [78], however restrictions have been placed by the European Medical Agency regarding administration to patients with existing heart disease [79]. Based on the association with AN and cardiac and nervous system disturbances [80], this review would not recommend Strontium Ranelate to increase BMD in adults or adolescents with AN.…”
Section: Strontium Ranelatementioning
confidence: 99%
“…Strontium Ranelate is effective in increasing BMD in post-menopausal women [78], however restrictions have been placed by the European Medical Agency regarding administration to patients with existing heart disease [79]. Based on the association with AN and cardiac and nervous system disturbances [80], this review would not recommend Strontium Ranelate to increase BMD in adults or adolescents with AN.…”
Section: Strontium Ranelatementioning
confidence: 99%
“…Despite its low toxicity, the drug was discontinued by the producer after the European Medicines Agency reported a slight increase (from 1.1 to 1.7% ) in cardiovascular events involving 7000 tested patients who used placebo or strontium ranelate, respectively. For this reason, it has been recommended as a therapeutic drug only for the treatment of severe cases of osteoporosis, for patients without cardiovascular contraindications.…”
Section: Introductionmentioning
confidence: 99%
“…Regarding the safety of SR, in vivo studies using rat models reported that the systemic use of SR (up to 625 g/kg daily) is well tolerated and safe, with no adverse effects . In a recent review of studies on the clinical use of SR for the management of osteoporosis (2 g/day), Reginster et al (2015) concluded that SR has an excellent benefit‐risk ratio, provided that its contraindications, including uncontrolled hypertension and a history of ischemic episodes, are respected.…”
Section: Discussionmentioning
confidence: 99%